Lines Drawn in Blood: A Comparative Perspective on the Accommodation of Blended Families in Succession Law - Cárdenas, Laura (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2020)
Blended families, created by the coupling of individuals with children who are not common to both spouses, are not new to Canadian society. Yet, Canadian legal systems still struggle to find ways of accounting for their specificities in various legal regimes. This article focuses on the way laws on inheritance treat blended families: whether a stepchild can inherit, upon intestacy, from the father they grew up with if he is not listed on their birth certificate; whether, as intended, the child of one of the spouses really receives their parent’s full estate if this parent predeceases their spouse; whether an intestate’s younger “half-sister” receives as much as an estranged older sibling. I take a comparative approach to these questions, critically analyzing laws across Canada, France, England, and Scotland to discuss the strengths and shortcomings of various legislative approaches.My findings indicate that while blended families create new relationships that are inexistent in the nuclear family, the template for succession laws across the world remains the nuclear family. Yet, even the simple parental relationship, when placed in the unique framework of a blended family, functions differently in this context and can lead to the rerouting of a deceased’s inheritance. This in-depth look at the interplay of blended families and contemporary succession laws, their origins, and purposes allows me to evaluate whether Canadian laws are accomplishing their goals when it comes to blended families. I find that our laws on inheritance often fail to accommodate the specificity of blended families, and suggest a reframing of the way we approach inheritance so as to foster their inclusion.